PEMBERDAY AAN HUKUM KONTRAK ALIH KETRAMPILAN DALAM RANGKA PENINGKATAN KUALITAS SUMBER DAYA MANUSIA - Emy Handayani (Faculty of Law, Universitas Diponegoro, 2011)
Law Empowerment pass through know-how use consensual principle to foreign technology adopt which transferring from foreign side, which one contract know-how compose for technology of result product by one business as raising quality for upgrading human resource bring aboard bussiness operational, have knowledge, ability and high- skill with my innovation and creativitas, with the result innovation capable and creative until quality result product in Global Market. Chaise research of method is qualitatif research of method with research characteristic socio-legal research. lnforman election as primery database at focus of research study.